A tripod ester terephthalic acid ligand and its preparation method as well as a preparation method and application of polylactic acid nanoluminescent fiber material

By using a method of combining tripodester terephthalic acid ligands with rare earth ions in polylactic acid fibers, physical cross-linking points are formed and rare earth luminescent materials are generated in situ, which solves the problems of long-term storage and performance monitoring of polylactic acid fibers. The excellent luminescent function and long-term performance maintenance of the polylactic acid nanoluminescent fiber material are achieved.

CN118359502BActive Publication Date: 2025-01-24XIAMEN XULUNCHENG TEXTILE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410504372.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-25
Publication Date
2025-01-24
Estimated Expiration
2044-04-25

AI Technical Summary

Technical Problem

How to prepare polylactic acid luminescent fiber materials with good luminescence function and long-term use performance to solve the challenges of long-term storage and performance monitoring of polylactic fibers.

Method used

The combination of trioprodelin phenyl acid ligands and rare earth ions are used to match the ester group in the PLA polymer chain through rare earth ions to form a physical cross -linking point to improve the stability of PLA fiber, and in the spinning process process The Central Plains generates three -footed rare earth luminescence materials, which is evenly scattered in the PLA spinning solution.

Benefits of technology

It achieves the maintenance of excellent luminescence function and long-term performance of polylactic acid nanoluminescent fiber materials, improves the stability of the fiber and the durability of luminescent performance, and solves the problems of long-term storage and performance monitoring of polylactic acid fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118359502B_ABST
    Figure CN118359502B_ABST
Patent Text Reader

Abstract

The present invention discloses a polylactic acid nano-luminescent fiber material and a preparation method and application thereof. The structure of the luminescent fiber material is as follows: the present invention forms physical crosslinking points between PLA polymer chains by coordinating rare earth Ln ions (europium, terbium, samarium and dysprosium ions) with ester groups in the PLA polymer chain structure. The effect of the physical crosslinking points makes the structure of PLA more stable, and also prevents the rare earth luminescent material from precipitating between the PLA polymer chains. In addition, the rare earth ions can also coordinate and absorb water molecules in the polylactic acid, thereby avoiding the hydrolysis of the polylactic acid, making its structural performance more stable and extending its service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polylactic acid nanofibers, and more specifically to a tripod ester terephthalic acid ligand and a preparation method thereof, as well as a preparation method and application of a polylactic acid nanoluminescent fiber material. Background Art

[0002] With the development of science and technology, fiber products have evolved from natural fibers, artificial fibers, and differentiated fibers to the era of high-tech fibers, and fiber products with multiple functions have also emerged. Among the many high-tech fibers, fiber products with photoluminescent functions have been widely used in many fields such as fluorescent anti-counterfeiting, fingerprint recognition, bio-imaging, sensors, and smart clothing. At the same time, with the design and synthesis of new luminescent materials, fiber products with photoluminescent functions have also made great progress. As the core material of photoluminescent fibers, the structure and properties of photoluminescent materials will directly determine the photoluminescent properties of the final fiber products, and the type of fiber-forming polymer will also limit the application field of photoluminescent fibers.

[0003] At present, most polymers used in polymer-based photoluminescent fibers are prepared from monomers obtained from petroleum resources. If petroleum resources are exhausted, there will inevitably be a risk of raw material shortage, which will be a huge challenge to the sustainable development of polymer-based photoluminescent fibers. Among polymers from sustainable biological sources, the synthetic monomers of polylactic acid can be obtained from biomass raw materials and have formed an industrial scale. The good processing properties of polylactic acid also make it the first choice for fiber-forming polymers in new photoluminescent fibers.

[0004] Polylactic acid contains ester groups in its molecular structure and is easily degraded when exposed to water, which poses an important challenge to the long-term storage and performance monitoring of polylactic acid fibers.

[0005] Therefore, how to prepare polylactic acid luminescent fiber materials with good luminescent function and long-term performance is an important issue in the development of new luminescent fiber products. Summary of the invention

[0006] In view of this, the present invention provides a polylactic acid nano-micron luminescent fiber material doped with a tripod ester rare earth luminescent material having excellent luminescent function and long-term performance, as well as a preparation method and application thereof.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A tripodal ester terephthalic acid ligand, the structure of which is as follows:

[0009]

[0010] The preparation method of the above tripod ester terephthalic acid ligand,

[0011]

[0012] The specific steps include:

[0013] 1) At room temperature, 4-formylbenzoic acid (6.00 g, 40 mmol), glycerol (0.92 g, 10 mmol), 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride (7.66 g, 4.410 mmol) and 4-dimethylaminopyridine (36 mg, 0.29 mmol) were dispersed and dissolved in 80 mL of CH2Cl2, and the mixture was stirred at room temperature for 24 h. Then, the reaction mixture was poured into a cold 5% HCl solution and extracted with CH2Cl2. The extract was washed with water, dried and evaporated, and the residual product was purified by a chromatographic column layer plate method (volume ratio of petroleum ether and ethyl acetate = 2:1) to obtain a colorless powder sample;

[0014] 2) A colorless powder sample (0.98 g, 2.0 mmol) and resorcinol (0.86 g, 7.8 mmol) were dissolved in 50 mL of tetrahydrofuran, and a solution of sodium chlorite (3.12 g, 34.5 mmol) and sodium dihydrogen phosphate monohydrate (0.83 g, 6.0 mmol) was added dropwise to the solution for more than 10 min. The resulting light yellow reaction mixture was stirred at room temperature overnight, and the volatile components were removed in vacuo. The residue was dissolved in 100 mL of water, and 1 M hydrochloric acid was added to acidify the aqueous solution to pH = 2. The white precipitate was filtered, washed with water, and then dried in air to obtain a white powder product.

[0015] The tripod ester terephthalic acid ligand provided by the present invention can carry more rare earth ions for coordination due to the presence of three carboxylic acid groups. At the same time, the rare earth ions have good coordination ability with the ester groups in the PLA polymer chain, thereby protecting the ester groups in the PLA polymer chain and solving the problem of long-term storage of PLA fibers.

[0016] Another object of the present invention is to provide a method for preparing a polylactic acid nano-luminescent fiber material, comprising the following steps:

[0017] (1) drying polylactic acid and tripod terephthalic acid ligands for standby use;

[0018] (2) adding polylactic acid to a mixed solvent, stirring the mixture to obtain a polylactic acid spinning solution, adding a tripod terephthalic acid ligand and a rare earth nitrate hydrate to the solution, and stirring the mixture at 40° C. to obtain a spinning solution;

[0019] (3) The prepared spinning solution is subjected to spinning treatment to obtain a polylactic acid nano-micron luminescent fiber membrane. After the spinning is completed, the sample is taken out and placed in a drying oven for drying to obtain the polylactic acid nano-luminescent fiber material.

[0020] The structure of the polylactic acid nanoluminescent fiber material prepared by the present invention is as follows:

[0021]

[0022] In the above formula, Ln represents a rare earth ion.

[0023] Preferably, the weight average molecular weight of the polylactic acid is >80,000 to 100,000 g / mol.

[0024] Preferably, the mass fraction of the polylactic acid spinning solution is 9%; the mixed solvent is a mixed solution of DCM and DMF, and the mass ratio thereof is (9:5) to (9:1).

[0025] Preferably, the molar ratio of the tripod ester terephthalic acid ligand to the rare earth nitrate hydrate is 1:3.

[0026] Preferably, the rare earth ion in the rare earth nitrate hydrate is europium, terbium, samarium or dysprosium.

[0027] Europium and terbium have strong rare earth ion characteristic fluorescence, narrow spectral band, high color purity, long excited state lifetime, and the fluorescence emission energy level of europium and terbium ions is close to the triplet energy level of the tripod ester terephthalic acid ligand in this patent, with strong ability to absorb excitation energy and high conversion rate.

[0028] Preferably, the mass of the in-situ generated tripod ester rare earth luminescent material doped in the spinning solution in step (2) is 2%, 4%, 6%, 8% or 10% of the mass of the polylactic acid.

[0029] Preferably, the spinning process includes: loading the spinning solution into a 5mL plastic syringe, connecting a 22G stainless steel needle to the syringe, spinning according to the process parameters of a spinning voltage of 18-22kV, a push injection speed of 0.0016-0.0020mm / s, and a receiving distance of 15-20cm, the spinning temperature is 25-32°C, and the humidity is 30-45%; the inner diameter of the stainless steel needle is 0.41mm.

[0030] In the present technology, rare earth nitrates and novel tripod ester terephthalic acid ligands are added to a PLA solution and mixed evenly, and the preparation of the tripod ester rare earth luminescent material is carried out in situ during the preparation of the spinning solution. This not only allows the rare earth luminescent material to be evenly dispersed in the PLA spinning solution, but also achieves a uniform distribution of the tripod ester rare earth luminescent material between PLA polymer chains through the coordination effect between the rare earth ions and the ester groups in the PLA polymer chains, thereby improving the durability of the luminescent performance of the PLA nanoluminescent fiber.

[0031] Another object of the present invention is to provide an application of the above-mentioned polylactic acid nano luminescent fiber material, specifically comprising:

[0032] 1. The fiber film products made of polylactic acid nano-micron luminous fiber materials can be used as intelligent anti-counterfeiting packaging materials;

[0033] 2. Since the polylactic acid nano-micron luminescent fiber material has good hydrophobicity, it can be used for oil-water separation and waste oil recovery;

[0034] 3. Based on the good biodegradability of polylactic acid and the property that rare earth complexes can convert ultraviolet light in sunlight into red and orange light required for plant photosynthesis, polylactic acid nano-micron luminescent fiber materials also have good application prospects in agricultural mulch films.

[0035] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present invention forms physical crosslinking points between PLA polymer chains by coordinating rare earth ions with ester groups in the PLA polymer chain structure. The effect of such physical crosslinking points makes the PLA structure more stable and also prevents the rare earth luminescent material from precipitating between PLA polymer chains. In addition, the rare earth ions can also coordinate and absorb water molecules in polylactic acid, thereby avoiding the hydrolysis of polylactic acid, making its structural performance more stable and extending its service life;

[0037] (2) In the present invention, since rare earth ions have good coordination with water molecules, during the storage of the polylactic acid nano-micron luminescent fiber material doped with the tripod ester rare earth luminescent material, a small amount of water molecules adsorbed by the PLA polymer will be fixed by coordination with the rare earth ions, and will not cause degradation to the PLA polymer chain itself. This makes the polylactic acid nano-micron luminescent fiber more conducive to long-term storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0039] Figure 1 This is the H-NMR spectrum of the tripodal ester terephthalic acid ligand;

[0040] Figure 2 This is the infrared spectrum of the tripodal ester terephthalic acid ligand;

[0041] Figure 3 The infrared spectrum of polylactic acid nanoluminescent fiber material doped with tripod ester rare earth luminescent material;

[0042] Figure 4 This is a SEM photo of a polylactic acid nanoluminescent fiber material doped with 2wt% of a tripod ester terbium luminescent material;

[0043] Figure 5 The fluorescence excitation (left) and emission (right) spectra of polylactic acid nano-luminescent fiber material doped with 2wt% tripod ester terbium luminescent material;

[0044] Figure 6 This is a SEM photo of a polylactic acid nanoluminescent fiber material doped with 4 wt% of a tripod ester terbium luminescent material;

[0045] Figure 7 The fluorescence excitation (left) and emission (right) spectra of polylactic acid nano-luminescent fiber material doped with 4 wt% of tripod ester terbium luminescent material;

[0046] Figure 8 This is a SEM photo of a polylactic acid nanoluminescent fiber material doped with 6wt% of a tripod ester terbium luminescent material;

[0047] Fig. 9 The fluorescence excitation (left) and emission (right) spectra of polylactic acid nano-luminescent fiber material doped with 6wt% tripod ester terbium luminescent material;

[0048] Fig.10 This is a SEM photo of a polylactic acid nanoluminescent fiber material doped with 8 wt% of a tripod ester terbium luminescent material;

[0049] Fig.11 The fluorescence excitation (left) and emission (right) spectra of polylactic acid nano-luminescent fiber material doped with 8wt% tripod ester terbium luminescent material;

[0050] Fig.12This is a SEM photo of a polylactic acid nanoluminescent fiber material doped with 10 wt% of a tripod ester terbium luminescent material;

[0051] Fig.13 The fluorescence excitation (left) and emission (right) spectra of polylactic acid nano-luminescent fiber material doped with 10wt% of tripod ester terbium luminescent material;

[0052] Fig.14 This is a SEM photo of a polylactic acid nanoluminescent fiber material doped with 6wt% of a tripod ester europium luminescent material;

[0053] Fig.15 Infrared spectrum of polylactic acid nano-luminescent fiber doped with 6wt% tripod ester europium luminescent material

[0054] Fig.16 The fluorescence excitation (left) and emission (right) spectra of polylactic acid nano-luminescent fiber material doped with 6wt% tripod ester europium luminescent material;

[0055] Fig.17 The photos are for testing the acid resistance, alkali resistance and water resistance of the polylactic acid nano luminescent fiber material provided by the present invention. DETAILED DESCRIPTION

[0056] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0057] Example 1

[0058] The tripod ester terephthalic acid ligand used in the present invention is prepared by the following method:

[0059]

[0060] (1) At room temperature, 4-formylbenzoic acid (6.00 g, 40 mmol), glycerol (0.92 g, 10 mmol), 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride (7.66 g, 4.410 mmol) and 4-dimethylaminopyridine (36 mg, 0.29 mmol) were dispersed and dissolved in 80 mL of CH2Cl2, and the mixture was stirred at room temperature for 24 h. Then, the reaction mixture was poured into a cold 5% HCl solution and extracted with CH2Cl2; the extract was washed with water, dried and evaporated; the residual product was purified by a chromatographic column layer plate method (volume ratio of petroleum ether and ethyl acetate = 2:1) to obtain a colorless powder sample;

[0061] (2) The oxide (0.98 g, 2.0 mmol) and resorcinol (0.86 g, 7.8 mmol) were dissolved in 50 mL of tetrahydrofuran; a solution of sodium chlorite (3.12 g, 34.5 mmol) and sodium dihydrogen phosphate monohydrate (0.83 g, 6.0 mmol) was added dropwise to the solution for more than 10 min; the resulting light yellow reaction mixture was stirred at room temperature overnight; the volatile components were removed in vacuo, and the residue was dissolved in 100 mL of water; 1 M hydrochloric acid was added to acidify the aqueous solution to pH = 2; the white precipitate was filtered, washed with water, and then dried in air to obtain a white powder product.

[0062] Example 2

[0063] Preparation of polylactic acid nano-luminescent fibers doped with 2 wt% tripod ester terbium luminescent material:

[0064] (1) placing polylactic acid and tripod terephthalic acid ligands in a blast drying oven for drying; weighing 1 kg of PLA and adding it into 10 kg of a mixed solvent (DCM:DMF=9:5), stirring them thoroughly to obtain polylactic acid spinning solutions with a mass fraction of 9%;

[0065] (2) adding 7.9200 g of a tripod ester terephthalic acid ligand and 20.0656 g of terbium nitrate hexahydrate to a polylactic acid spinning stock solution, and continuously stirring the solution with a magnetic stirrer at 40° C. to obtain a spinning solution; the mass of the tripod ester rare earth luminescent material generated in situ is 2% of the mass of the polylactic acid;

[0066] (3) The prepared spinning solution is loaded into multiple rows of syringes of uniform specifications, each with a capacity of 100 mL; a 22G stainless steel needle (inner diameter 0.41 mm) is connected to the syringe; spinning is performed according to the process parameters of spinning voltage of 18 kV, injection speed of 0.0016 mm / s, receiving distance of 15 cm, spinning temperature of 25° C., and humidity of 30%; the obtained polylactic acid nano-micron luminescent fiber film is formed on a drum receiver. After spinning is completed, the sample is removed from the collecting device and placed in a vacuum drying oven for drying.

[0067] Example 3

[0068] Preparation of polylactic acid nano-luminescent fibers doped with 4wt% tripod ester terbium luminescent material:

[0069] (1) placing polylactic acid and tripod terephthalic acid ligands in a blast drying oven for drying; weighing 1 kg of PLA and adding it into 10 kg of a mixed solvent (DCM:DMF=9:1), stirring them thoroughly to obtain polylactic acid spinning solutions with a mass fraction of 9%;

[0070] (2) adding 16.1704 g of a tripod ester terephthalic acid ligand and 40.9684 g of terbium nitrate hexahydrate to a polylactic acid spinning stock solution, and continuously stirring the solution at 40° C. using a magnetic stirring device; the mass of the in-situ generated tripod ester rare earth luminescent material is 4% of the mass of the polylactic acid;

[0071] (3) The prepared spinning solution is loaded into multiple rows of syringes of uniform specifications, each with a capacity of 100 mL; a 22G stainless steel needle (inner diameter 0.41 mm) is connected to the syringe; spinning is carried out according to the process parameters of spinning voltage of 22 kV, injection speed of 0.0020 mm / s, receiving distance of 20 cm, spinning temperature of 32°C, and humidity of 45%; the obtained polylactic acid nano-micron luminescent fiber membrane is formed on a drum receiver; after spinning is completed, the sample is removed from the collecting device and placed in a vacuum drying oven for drying.

[0072] Example 4

[0073] Preparation of polylactic acid nano-luminescent fibers doped with 6wt% tripod ester terbium luminescent material:

[0074] (1) placing polylactic acid and tripod terephthalic acid ligands in a blast drying oven for drying; weighing 1 kg of PLA and adding it into 10 kg of a mixed solvent (DCM:DMF=9:3), stirring them thoroughly to obtain polylactic acid spinning solutions with a mass fraction of 9%;

[0075] (2) adding 24.7717 g of a tripod ester terephthalic acid ligand and 62.7600 g of terbium nitrate hexahydrate to a polylactic acid spinning stock solution, and continuously stirring the solution at 40° C. using a magnetic stirring device to obtain a spinning solution; the mass of the in-situ generated tripod ester rare earth luminescent material is 6% of the mass of the polylactic acid;

[0076] (3) The prepared spinning solution is loaded into multiple rows of syringes of uniform specifications, each with a capacity of 100 mL; a 22G stainless steel needle (inner diameter 0.41 mm) is connected to the syringe; spinning is carried out according to the process parameters of spinning voltage of 20 kV, injection speed of 0.0018 mm / s, receiving distance of 18 cm, spinning temperature of 30°C, and humidity of 38%; the obtained polylactic acid nano-micron luminescent fiber membrane is formed on a drum receiver; after spinning is completed, the sample is removed from the collecting device and placed in a vacuum drying oven for drying.

[0077] Example 5

[0078] Preparation of polylactic acid nano-luminescent fibers doped with 8 wt% tripod ester terbium luminescent material:

[0079] (1) placing polylactic acid and tripod terephthalic acid ligands in a blast drying oven for drying; weighing 1 kg of PLA and adding it into 10 kg of a mixed solvent (DCM:DMF=9:4), stirring them thoroughly to obtain polylactic acid spinning solutions with a mass fraction of 9%;

[0080] (2) adding 33.7474 g of a tripod ester terephthalic acid ligand and 85.5004 g of terbium nitrate hexahydrate to a polylactic acid spinning stock solution, and continuously stirring the solution at 40° C. using a magnetic stirring device; the mass of the in-situ generated tripod ester rare earth luminescent material is 8% of the mass of the polylactic acid;

[0081] (3) The prepared spinning solution is loaded into multiple rows of syringes of uniform specifications, each with a capacity of 100 mL; a 22G stainless steel needle (inner diameter 0.41 mm) is connected to the syringe; spinning is carried out according to the process parameters of spinning voltage of 21 kV, injection speed of 0.0019 mm / s, receiving distance of 20 cm, spinning temperature of 31°C, and humidity of 32%; the obtained polylactic acid nano-micron luminescent fiber membrane is formed on a drum receiver; after spinning is completed, the sample is removed from the collecting device and placed in a vacuum drying oven for drying.

[0082] Example 6

[0083] Preparation of 10wt% polylactic acid nanoluminescent fiber doped with tripod ester terbium luminescent material:

[0084] (1) placing polylactic acid and tripod terephthalic acid ligands in a blast drying oven for drying; weighing 1 kg of PLA and adding it into 10 kg of a mixed solvent (DCM:DMF=9:3), stirring them thoroughly to obtain polylactic acid spinning solutions with a mass fraction of 9%;

[0085] (2) adding 43.1190 g of a tripod ester terephthalic acid ligand and 109.2437 g of terbium nitrate hexahydrate to a polylactic acid spinning stock solution, and continuously stirring the solution at 40° C. using a magnetic stirring device; the mass of the in-situ generated tripod ester rare earth luminescent material is 10% of the mass of the polylactic acid;

[0086] (3) The prepared spinning solution is loaded into multiple rows of syringes of uniform specifications, each with a capacity of 100 mL; a 22G stainless steel needle (inner diameter 0.41 mm) is connected to the syringe; spinning is carried out according to the process parameters of spinning voltage of 20 kV, injection speed of 0.0017 mm / s, receiving distance of 18 cm, spinning temperature of 32°C, and humidity of 35%; the obtained polylactic acid nano-micron luminescent fiber membrane is formed on a drum receiver; after spinning is completed, the sample is removed from the collecting device and placed in a vacuum drying oven for drying.

[0087] Example 7

[0088] Preparation of polylactic acid nano-luminescent fibers doped with 6wt% tripod ester europium luminescent material:

[0089] (1) placing polylactic acid and tripod terephthalic acid ligands in a blast drying oven for drying; weighing 1 kg of PLA and adding it into 10 kg of a mixed solvent (DCM:DMF=9:1), stirring them thoroughly to obtain polylactic acid spinning solutions with a mass fraction of 9%;

[0090] (2) adding 25.1518 g of a tripod ester terephthalic acid ligand and 62.7440 g of europium nitrate hexahydrate to a polylactic acid spinning stock solution, and continuously stirring the solution at 40° C. using a magnetic stirring device; the mass of the in-situ generated tripod ester rare earth luminescent material is 6% of the mass of the polylactic acid;

[0091] (3) The prepared spinning solution is loaded into multiple rows of syringes of uniform specifications, each with a capacity of 100 mL; a 22G stainless steel needle (inner diameter 0.41 mm) is connected to the syringe; spinning is carried out according to the process parameters of spinning voltage of 22 kV, injection speed of 0.0020 mm / s, receiving distance of 18 cm, spinning temperature of 28 ° C, and humidity of 30-45%; the obtained polylactic acid nano-micron luminescent fiber membrane is formed on a drum receiver; after spinning is completed, the sample is removed from the collecting device and placed in a vacuum drying oven for drying.

[0092] The obtained product was tested for acid resistance, alkali resistance and water resistance. Fig.17 The first three are samples of polylactic acid nano-luminescent fibers with added tripod ester rare earth luminescent materials, and the last one is a sample of pure polylactic acid nano-luminescent fibers. As can be seen from the figure, the pure polylactic acid nano-luminescent fibers began to decompose after 3 days.

[0093] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0094] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A tripodal ester terephthalic acid ligand, characterized in that: The structure of the tripod ester terephthalic acid ligand is as follows:

2. The method for preparing a tripodal ester terephthalic acid ligand according to claim 1, characterized in that: The synthetic route is as follows: The specific steps include: 1) Disperse and dissolve 4-formylbenzoic acid, glycerol, 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide and 4-dimethylaminopyridine in CH2Cl2 at room temperature, and stir the mixture for reaction at room temperature for 24 hours; then, pour the reaction mixture into a cold 5% HCl solution and extract with CH2Cl2; then, wash, dry and purify to obtain a colorless powder sample; 2) The colorless powder sample and resorcinol are dissolved in tetrahydrofuran, and then a solution of sodium chlorite and sodium dihydrogen phosphate is added dropwise to the solution for more than 10 minutes, and then the resulting light yellow reaction mixture is stirred at room temperature overnight, and the volatile components are removed. The residue is dissolved in water, and hydrochloric acid is added to acidify the aqueous solution to pH = 2, and then filtered and dried to obtain the tripod ester terephthalic acid ligand.

3. A method for preparing a polylactic acid nanoluminescent fiber material, characterized in that: The following steps are involved: (1) drying polylactic acid and the tripod ester terephthalic acid ligand according to claim 1 for later use; (2) adding polylactic acid to a mixed solvent, stirring the mixture to obtain a polylactic acid spinning solution, adding a tripod terephthalic acid ligand and a rare earth nitrate hydrate to the solution, and stirring the mixture at a certain temperature to obtain a spinning solution; (3) The prepared spinning solution is subjected to spinning treatment to obtain a polylactic acid nano-micron luminescent fiber membrane. After the spinning is completed, the sample is taken out and dried to obtain the polylactic acid nano-luminescent fiber material.

4. The method for preparing a polylactic acid nanoluminescent fiber material according to claim 3, characterized in that: The weight average molecular weight of the polylactic acid is greater than 80,000 to 100,000 g / mol.

5. The method for preparing a polylactic acid nanoluminescent fiber material according to claim 3, characterized in that: The mass fraction of the polylactic acid spinning solution is 9%; the mixed solvent is a mixed solution of DCM and DMF, and the mass ratio thereof is (9:5) to (9:1).

6. The method for preparing a polylactic acid nanoluminescent fiber material according to claim 3, characterized in that: The molar ratio of the tripod ester terephthalic acid ligand to the rare earth nitrate hydrate is 1:

3.

7. The method for preparing a polylactic acid nanoluminescent fiber material according to claim 3, characterized in that: The rare earth ions in the rare earth nitrate hydrate are europium, terbium, samarium or dysprosium.

8. The method for preparing a polylactic acid nanoluminescent fiber material according to claim 3, characterized in that: The stirring temperature in step (2) is 40° C.; the mass of the in-situ generated tripod ester rare earth luminescent material doped in the spinning solution is 2%, 4%, 6%, 8% or 10% of the mass of the polylactic acid.

9. The method for preparing a polylactic acid nanoluminescent fiber material according to claim 3, characterized in that: The spinning process comprises: loading a spinning solution into a 5 mL plastic syringe, connecting a 22G stainless steel needle to the syringe, spinning according to the process parameters of a spinning voltage of 18-22 kV, a push injection speed of 0.0016-0.0020 mm / s, and a receiving distance of 15-20 cm, a spinning temperature of 25-32° C., and a humidity of 30-45%; the inner diameter of the stainless steel needle is 0.41 mm.

10. Application of the polylactic acid nano-luminescent fiber material obtained by the preparation method of the polylactic acid nano-luminescent fiber material as claimed in claim 3 in intelligent anti-counterfeiting packaging materials, oil-water separation, waste oil recovery and agricultural mulch film.

Citation Information

Patent Citations

  • Nanometer fluorescence fiber material and preparation method thereof

    CN108547009A

  • Red mud treating agent, preparation method and applications thereof

    CN111138712A